1971
DOI: 10.1126/science.174.4007.412
|View full text |Cite
|
Sign up to set email alerts
|

Freezing and Melting of Lipid Bilayers and the Mode of Action of Nonactin, Valinomycin, and Gramicidin

Abstract: An abrupt loss of effectiveness of the presumed carriers, nonactin and valinomycin, in mediating ion conductance occurred at the same temperature as the membrane fluidity, judged visually, was lost. By contrast, the effects of the presumed channel-former, gramicidin, were the same on solid and liquid membranes. Taken together, these findings imply that freezing the membrane primarily reduces the mobility of these antibiotics with little effect on their solubility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
106
1
1

Year Published

1972
1972
1999
1999

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(115 citation statements)
references
References 27 publications
7
106
1
1
Order By: Relevance
“…5, the effect of nigericin also decreased as the incubation temperature was lowered. This was consistent with previous findings in this and other experimental systems (Krasne et al, 1971 ;Krulwich et al, 1978;Racker & Hinkle, 1974).…”
Section: Eflect Of External P H On Nigericin-induced Deathsupporting
confidence: 83%
“…5, the effect of nigericin also decreased as the incubation temperature was lowered. This was consistent with previous findings in this and other experimental systems (Krasne et al, 1971 ;Krulwich et al, 1978;Racker & Hinkle, 1974).…”
Section: Eflect Of External P H On Nigericin-induced Deathsupporting
confidence: 83%
“…In going beyond the temperature range accessible experimentally to Krasne et al (6), we also observed freezing effects with the gramicidininduced membrane conductance (Fig. 2A).…”
mentioning
confidence: 56%
“…Due to the instability of planar bilayer membranes in the solid state, there are so far only two reports on electrochemical measurements in the freezing and melting range of planar lipid bilayer membranes. Experiments carried out on membranes from a 1:1 (wt/wt) mixture of dipalmitoylglycerol and distearoylglycerol in n-decane led to the interpretation that ion carriers became frozen and thus immobile within the membrane phase (6). On the other hand, the ionic conductance induced by the pore-former gramicidin was found to remain unchanged at the transition temperature tc of 41'C.…”
mentioning
confidence: 92%
“…That biologically relevant transport processes can occur in rigid systems has recently been shown by Krasne et al [71], where it was demonstrated that the ion translocating antibiotic, gramicidin, was able to mediate potassium ion transport in both "solid" as well as "liquid" black lipid membranes.…”
Section: X-raymentioning
confidence: 89%